Leading on the edge : extraordinary stories and leadership insights from the world's most extreme workplace - Robertson, Rachael, 1969- (John Wiley & Sons Australia, 2014)
"In Leading on the Edge, successful business speaker and consultant Rachael Robertson shares the lessons she learned as leader of a year-long expedition to the wilds of Antarctica. Leading eighteen strangers around the clock for a full year, through months of darkness and with no escape from the frigid cold, howling winds, and each other, Robertson learned powerful lessons about what real, authentic leadership is. Here, she offers a deeply honest and humorous account of what it takes to survive and lead in the harshest environment on Earth. What emerges from her graphic account is a series of powerful and practical lessons for business leaders and managers everywhere"--Publisher's website